THE IMPORTANCE OF COMMUNICATIVE COMPETENCE IN TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) - G’ulomjonova Mohibonu G’ayratjonovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the importance of communicative competence in Teaching English for Specific Purposes (ESP), particularly for non-philological students. In modern higher education, learners from technical and non-linguistic fields require English not only for academic purposes but also for professional communication. The study discusses key theoretical frameworks of communicative competence and examines its role in ESP classrooms. The research highlights that communicative competence improves students’ ability to use English in real-life professional contexts, enhances speaking confidence, and supports task-based learning. The findings suggest that integrating communicative activities into ESP instruction significantly increases learners’ linguistic and pragmatic performance.